Prevalence of Thyroid Dysfunction among Patients with Type 2 Diabetes Mellitus in Diabetic Center in Prince Mansour Hospital and Diabetic Clinic in Primary Health Care in Iskan- Taif City, Saudi Arabia 2018 - A. Allah, Ahmed; Mansour, Prince; M. Alshehri, Khalid; O. Althomali, Reham; A. Alhamyani, Rawan; A. Alharthi, Atheer; S. Alzahrani, Sarah; A. Al Harthi, Mohammed; M. Almalki, Zohoor; M. Alwagdani, Maram (International Journal of Psychosocial Rehabilitation, 2019)
Abstract--- Background: Patients with DM are at an increased risk of thyroid disease (5). The frequency of thyroid dysfunction in diabetic patients is higher than that of the general population. Objectives: The present study aimed to assess the prevalence of thyroid dysfunction among diabetic in Taif city, Saudi Arabia. Methods: this study was conducted in the Diabetic Center in Prince Mansour hospital and Diabetic Clinic in Primary Health Care in Taif city. The sample size was 492 medical records of patients who attended the Diabetes clinic. a checklist was prepared for every medical records to collect data about age, gender, body mass index (BMI), and the presence of eye, kidney or neurological complications. The level of HbA1C, TSH, T4, T3 were reported for every patient. Results: 67.1% of the participants were females and 79.5% of them were suffering from eye disorders, 18.1% were suffering from kidney disorders, and 7.5% were suffering from neurological disorders. Of the participants, 58.9% had an euthyroid status, 31.1% had hypothyroidism, and 10% had hyperthyroidism. Female patients had a significant higher prevalence of thyroid disorders compared to male patients. A significant positive correlation was found between the mean level of HbA1C and the mean levels of T4, and a significant negative correlation was found between HbA1C and the mean levels of T3. Conclusion: The present study showed that thyroid disorders are more frequently diabetic patients especially females. Routine screening of all diabetic patients for thyroid function should be done to avoid the double burden of both diseases